Knowledge of Sarcopenia and Associated Factors among the Malaysian General Public: A Cross-sectional Study - Soon, Lean Keng; Noor Hazlisa, Che Seman *; K Mangaikresh, Krishnan *; Chook, Jack Bee *; Leong, Joyce Whye Sook; Siti Fairuz, Ismail; Ooi, Pei Boon *; Peh, Suat Cheng * (Korean Society for Preventive Medicine, 2023)
Objectives: Sarcopenia has emerged as a significant aging-related disease that affects many facets of societal-level and patient-level public health. This study analysed knowledge of sarcopenia and associated socio-demographic factors among the general public of Malaysia in order to effectively improve its prevention and countermeasures.